Mode selection by ohmic losses in longitudinally corrugated cavities of sub-THz second-harmonic gyrotrons - Tkachova, T.I.; Shcherbinin, V.I.; Tkachenko, V.I. (Вопросы атомной науки и техники, 2019)
Ohmic wall losses are proposed as a means for improving the mode selection in a cylindrical gyrotron cavity with longitudinal wedge-shaped corrugations. Such losses depend on mode frequency and geometrical parameters of the corrugations. For cavity of the 0.4-THz second-harmonic gyrotron we find the corrugation depth, which corresponds to maximum ohmic losses of the competing modes excited at the first (fundamental) cyclotron resonance, as well as to reasonably low losses of the operating mode. For this depth, we determine the number of corrugations and their width, which ensure the maximum enhancement of the ohmic wall losses of the fundamental modes with respect to those of the operating second-harmonic mode, together with minimum conversion of the operating second-harmonic mode to higher Bloch harmonics. Parameters of the corrugations in hand are practicable. Запропоновано використання омічних втрат у стінках для поліпшення селекції мод у циліндричному резонаторі гіротрона з поздовжніми клиновидними гофрами. Такі втрати залежать від частоти моди та геометрії гофрів. Для резонатора 0.4-ТГц гіротрона на другій циклотронній гармоніці знайдено глибину гофрів, яка відповідає максимальним омічним втратам конкуруючих мод на першому (фундаментальному) циклотронному резонансі та досить низьким втратам робочої моди. Для цієї глибини визначено кількість гофрів та їх ширину, які забезпечують максимальне збільшення омічних втрат для фундаментальних конкуруючих мод відносно втрат робочої моди на другому циклотронному резонансі, а також мінімальну конверсію робочої моди у вищі гармоніки Блоха. Параметри гофрів можуть бути реалізовані на практиці. Предложено использовать омические потери в стенках для улучшения селекции мод в цилиндрическом резонаторе гиротрона с продольными клиновидными гофрами. Такие потери зависят от частоты моды и геометрии гофров. Для резонатора 0.4-ТГц гиротрона на второй циклотронной гармонике найдена глубина гофров, которая отвечает максимальным омическим потерям конкурирующих мод на первом (фундаментальном) циклотронном резонансе и достаточно низким потерям рабочей моды. Для этой глубины определены количество гофров и их ширина, которые обеспечивают максимальный прирост омических потерь для фундаментальных конкурирующих мод относительно потерь для рабочей моды на втором циклотронном резонансе, а также минимальную конверсию рабочей моды в высшие гармоники Блоха. Параметры гофров могут быть реализованы на практике.